Records of Burdigalian sea level and paleoclimate in the Maldives carbonate system - Wu, Feng; Jian, Zhimin; Xie, Xinong; Bialik, Or M.; Reolid, Jesús (Frontiers in Marine Science, 2024)
Tropical carbonate systems are valuable archives of paleoenvironments, as the carbonate growth is intimately affected by water depth and climatic conditions. Geochemical data from the Burdigalian interval in IODP Site U1468 in the Maldives, northern Indian Ocean, were integrated with sedimentological and paleontological data for a more detailed reconstruction of depositional history. Generally, the Sr/Ca values of slope sediments record highstand progradation in both sequence unit and whole Burdigalian interval, while the absence of higher Sr/Ca ratio close to the sequence boundary during the early Burdigalian could be related to the erosion of deeper-water sediments due to the activity of bottom current. From 20.5 to 19.1 Ma and from 17.9 to 17.2 Ma, nutrient level and productivity were moderately elevated due to the terrigenous input by the intensified South Asian Proto-Monsoon, which also helped cause more reducing conditions in the distal slope. Moreover, increased nutrient level facilitated the growths of calcareous algae and sponges, while it was not favorable for coral development. The elevated nutrient level, higher sea level, and monsoon-induced current contributed to the backstepping of the outer margin during the late Burdigalian. Our study shows an example on how a tropical carbonate platform evolved in response to the interplay of sea-level and paleoclimatic conditions. Findings are expected to be applicable to other tropical carbonate platforms.